2018
DOI: 10.1080/23808993.2018.1420419
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomic studies of hypertension: paving the way for personalized antihypertensive treatment

Abstract: The polygenic nature of antihypertensive drug response is a major barrier to clinical implementation. Further studies examining clinical effectiveness are required to support broad-based implementation of genotype-based prescribing in medical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 99 publications
0
11
0
Order By: Relevance
“…Antihypertensive pharmacogenomic variants were included for metoprolol ( CYP2D6 ), other beta-blockers ( GRK4 , ADRB1 ), hydralazine ( NAT2 ), losartan ( CYP2C9 ), amlodipine ( F7 ), thiazide diuretics ( YEATS4 , FGF5 / SH2B3 / EBF1 ), diuretics ( NEDD4L ), angiotensin-converting-enzyme inhibitors ( F7 ), and angiotensin II receptor blockers ( NPHS1 ) (Table 1) [3-11]. The clinical validity of these variants has been previously reviewed and their associated levels of evidence vary [12, 13]. For example, CYP2D6 -guided dosing of metoprolol has been recommended by the DPWG.…”
Section: Variant Selectionmentioning
confidence: 99%
“…Antihypertensive pharmacogenomic variants were included for metoprolol ( CYP2D6 ), other beta-blockers ( GRK4 , ADRB1 ), hydralazine ( NAT2 ), losartan ( CYP2C9 ), amlodipine ( F7 ), thiazide diuretics ( YEATS4 , FGF5 / SH2B3 / EBF1 ), diuretics ( NEDD4L ), angiotensin-converting-enzyme inhibitors ( F7 ), and angiotensin II receptor blockers ( NPHS1 ) (Table 1) [3-11]. The clinical validity of these variants has been previously reviewed and their associated levels of evidence vary [12, 13]. For example, CYP2D6 -guided dosing of metoprolol has been recommended by the DPWG.…”
Section: Variant Selectionmentioning
confidence: 99%
“…A complete list of genes, variants, and clinical phenotypes provided is included in Table 1. Evidence for these variants has been previously reviewed [11,17]. Variants with abundant evidence relevant to cardiovascular drugs were also included in the panel.…”
Section: Methodsmentioning
confidence: 99%
“…The KCNMB1 gene encodes the β1 subunit of the large-conductance potassium (BKor Maxi-K type) channel. It has been shown that reduced function of this protein is associated with diminished calcium sensitivity, higher BP, and cardiac hypertrophy [ 19 , 24 ]. Two nonsynonymous polymorphisms in the KCNMB1 gene—Glu65Lys (rs11739136) and Val110Leu (rs2301149)—were found to modulate inter-patient variability in BP response to verapamil.…”
Section: Calcium Channel Blocking Agentsmentioning
confidence: 99%
“…Candidate association studies revealed variants in the calcium channels that could facilitate the selection of a CCB or β-blocker—for example, in CACNA1C , which encodes the alpha1c-subunit of the L-type calcium channel [ 24 ]. Beitelshees et al [ 25 ] screened eight single-nucleotide polymorphisms within CACNA1C to search for the relationship between verapamil and atenolol treatment efficacy and the occurrence of primary outcomes of stroke, myocardial infarction, and death.…”
Section: Calcium Channel Blocking Agentsmentioning
confidence: 99%
See 1 more Smart Citation